1992
DOI: 10.1007/bf02403673
|View full text |Cite
|
Sign up to set email alerts
|

Ordering and structural transformations in Ni3Al alloys

Abstract: X-ray diffraction profile studies on the filings of stoichiometric and off-stoichiometric compositions of Ni3AI alloys, with and without boron additions, were conducted to clarify some of the significant anomalies noticed in the literature. The long-range order parameter was estimated as a function of temperature in all the four alloys from (1 00)/(200) and (1 1 0)/(2 2 0) pairs of reflections. The L 12 structure appears to attain a maximum stability at about 600 ~ around which temperature its order parameter … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
11
0

Year Published

1994
1994
2016
2016

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 26 publications
(13 citation statements)
references
References 15 publications
2
11
0
Order By: Relevance
“…Diffraction patterns were found to be consistent with cubic Pm-3m(g 0 ) and Fm3m(g) structures. Lebail fitting using GSAS [24] resulted in a ¼ 3.567 ± 0.005 Å and v ¼ 45.38 ± 0.05 Å 3 in agreement with literature values [25,26]. In-situ X-ray diffraction studies were carried out on NieAleCr using diamond anvil cell at beamline 12.2.2, of Advanced Light Source (ALS), LBNL employing angle dispersive geometry using wavelength of 0.4959 Å.…”
Section: Methodssupporting
confidence: 75%
“…Diffraction patterns were found to be consistent with cubic Pm-3m(g 0 ) and Fm3m(g) structures. Lebail fitting using GSAS [24] resulted in a ¼ 3.567 ± 0.005 Å and v ¼ 45.38 ± 0.05 Å 3 in agreement with literature values [25,26]. In-situ X-ray diffraction studies were carried out on NieAleCr using diamond anvil cell at beamline 12.2.2, of Advanced Light Source (ALS), LBNL employing angle dispersive geometry using wavelength of 0.4959 Å.…”
Section: Methodssupporting
confidence: 75%
“…It has been shown by Sato and Toth [28] and Beattie [29], that by creating an APB of 1/2h110i on every alternate (001) plane, L1 2 structure can be transformed to DO 22 structure. The stability of DO 22 structure of Ni 76 Al 24 (B) can also be inferred from the work of Ramesh et al [5]. They observed that high temperature annealing of filed powders of a Ni 76 Al 24 alloy led to changes in the relative intensities of {200} and {220} peaks as a function of the temperature of annealing.…”
Section: Crystal Structurementioning
confidence: 85%
“…However, there are inconsistent reports regarding the stability of ordered Ni 3 Al. Kornilov and Mints [4] first reported from their dilatometric study that there is a solid-state phase transformation at about 600 C. Ramesh et al [5,6] reported about the presence of such transformation by X-ray analysis. They hypothetically proposed that the transformed structure is another ordered tetragonal structure.…”
Section: Introductionmentioning
confidence: 99%
“…The following relationship was used for the calculation of S: [16] of the same alloy, which was previously subjected to heavy 2 } amounts of cold deformation. Specifically, the changes in order and crystallographic texture, consequent upon anneal-…”
Section: Introductionmentioning
confidence: 99%